Cryo-EM structure of Sudan ebolavirus glycoprotein complexed with its human endosomal receptor NPC1 - Fan Bu; Gang Ye; Hailey Turner-Hubbard; Morgan Herbst; Bin Liu; Fang Li (Communications Biology)
Abstract Sudan ebolavirus (SUDV), like Ebola ebolavirus (EBOV), poses a significant threat to global health and security due to its high lethality. However, unlike EBOV, there are no approved vaccines or treatments for SUDV, and its structural interaction with the endosomal receptor NPC1 remains unclear. This study compares the glycoproteins of SUDV and EBOV (in their proteolytically primed forms) and their binding to human NPC1 (hNPC1). The findings reveal that the SUDV glycoprotein binds significantly more strongly to hNPC1 than the EBOV glycoprotein. Using cryo-EM, we determined the structure of the SUDV glycoprotein/hNPC1 complex, identifying four key residues in the SUDV glycoprotein that differ from those in the EBOV glycoprotein and influence hNPC1 binding: Ile79, Ala141, and Pro148 enhance binding, while Gln142 reduces it. Collectively, these residue differences account for SUDV’s stronger binding affinity for hNPC1. This study provides critical insights into receptor recognition across all viruses in the ebolavirus genus, including their interactions with receptors in bats, their suspected reservoir hosts. These findings advance our understanding of ebolavirus cell entry, tissue tropism, and host range.